Interaction between contrasting rice genotypes and soil physical conditions induced by hydraulic stresses typical of alternate wetting and drying irrigation of soil - Fang, Huan; Zhou, Hu; Norton, Gareth J.; Price, Adam H.; Raffan, Annette C.; Mooney, Sacha J.; Peng, Xinhua; Hallett, Paul D. (Springer, 2018)
Background and aims: Alternate wetting and drying (AWD) saves water in paddy rice production but could influence soil physical conditions and root growth. This study investigated the interaction between contrasting rice genotypes, soil structure and mechanical impedance influenced by hydraulic stresses typical of AWD. Methods: Contrasting rice genotypes, IR64 and deeper- rooting Black Gora were grown in various soil conditions for 2 weeks. For the AWD treatments the soil was either maintained in a puddled state, equilibrated to −5 kPa (WET), or dried to −50 kPa and then rewetted at thewater potential of −5 kPa (DRY-WET). There was an additional manipulated macropore structure treatment, i.e. the soil was broken into aggregates, packed into cores and equilibrated to −5 kPa (REPACKED). A flooded treatment (puddled soil remained flooded until harvest) was set as a control (FLOODED). Soil bulk density, penetration resistance and X-ray Computed Tomography (CT) derived macropore structure were measured. Total root length, root surface area, root volume, average diameter, and tip number were determined by WinRhizo. Results: AWD induced formation of macropores and slightly increased soil mechanical impedance. The total root length of the AWD and REPACKED treatments were 1.7–2.2 and 3.5–4.2 times greater than that of the FLOODED treatment. There was no significant difference between WET and DRY-WET treatments. The differences between genotypes were minimal. Conclusions: AWD influenced soil physical properties and some root characteristics of rice seedlings, but drying soil initially to −50 kPa versus −5 kPa had no impact. Macropores formed intentionally from repacking caused a large change in root characteristics.